Padronização de teste in vitro para avaliação da eficácia de produtos tópicos usados na eliminação de larvas de Cochliomyia hominivorax - Nogueira, Sabrina Nathália Louzada (2018)
The exploration of new alternatives that aim at the decrease in the number of animals used in research is increasing. In the present days, tests that prove the effectiveness of an antiparasitic for the elimination of larvae of Cochliomyia hominivorax, parasite that generates great damages in the veterinary medicine, are performance using several animals. Thus, the objective of this work was to standardize an in vitro test to evaluate the larvicidal efficacy of products used by topical route against Cochliomyia hominivorax larvae. In order to do this, five commercial products were analyzed, each product was evaluated in vitro. In three replicates for each larval stage (L1, L2 and L3), in larvae from colony kept in the laboratory and, for comparative effect, besides the laboratory stage, in vivo tests were performed with natural infestations in scrotal wounds caused by orchiectomy, treated with the same commercial products used in the in vitro test. The in vitro test results were compared to the in vivo test results and it was found that the applied tests showed similar results. Thus, it is concluded that the in vitro test can be adopted to evaluate efficacy against C. hominivorax larvae for topical products. Based on the results obtained in this study, the in vitro test will be presented to the Ministry of Agriculture Livestock and Supply and suggested as an alternative evaluation for topical products, allowing to decrease the use of animals in the tests for topical products.